2020
DOI: 10.21203/rs.3.rs-100577/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Warfarin Versus Direct Oral Anticoagulants for Treating Left Ventricular Thrombus: A Systematic Review and Meta-Analysis

Abstract: Background: Left ventricular thrombus (LVT) is not uncommon and pose a risk of systemic embolism, which can be mitigated by adequate anticoagulation. Direct oral anticoagulants (DOACs) are increasingly being used as alternatives to warfarin for anticoagulation, but their efficacy and safety profile has been debated. We aim to compare the therapeutic efficacy and safety of DOACs versus warfarin for the treatment of LVT.Methodology: We systematically searched PubMed/Medline, Google Scholar, Cochrane library, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…7,9,10,18,24,30 In a meta-analysis by Dalia et al, mortality was found to be 9% higher in patients receiving warfarin compared to those treated with DOACs (risk ratio 1.09, 95% CI 0.70-1.70), but the difference was not statistically significant. 36 This finding is in keeping with our results, which showed no significant mortality benefit with use of one anticoagulant over the other.…”
Section: Secondary Outcomessupporting
confidence: 92%
See 3 more Smart Citations
“…7,9,10,18,24,30 In a meta-analysis by Dalia et al, mortality was found to be 9% higher in patients receiving warfarin compared to those treated with DOACs (risk ratio 1.09, 95% CI 0.70-1.70), but the difference was not statistically significant. 36 This finding is in keeping with our results, which showed no significant mortality benefit with use of one anticoagulant over the other.…”
Section: Secondary Outcomessupporting
confidence: 92%
“…Previous meta-analyses have not examined stroke as an individual outcome, but rather a composite SSE, making this the first review to demonstrate this statistically significant difference. 7,[34][35][36] However, this finding must be contextualized by the limitations of the primary studies, including the inherent bias of cohort studies and the lack of an adjusted analysis. Further studies-ideally in the form of adequately powered RCTsare required to substantiate this finding.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…One nonfatal bleeding event and one stroke event were reported while on a DOAC. Secondly, a meta-analysis by Dalia et al, 21 which pooled data on 1955 patients from 8 studies, was executed in late 2020. This meta-analysis formulated the odds ratio for thrombus resolution and stroke/systemic embolization and bleeding in patients treated with warfarin vs DOACs, reporting that DOACs appear to be noninferior to, or at least as effective as, warfarin in efficacy without any statistical difference in either stroke or bleeding complications.…”
Section: Discussion and Limitationsmentioning
confidence: 99%